RETRACTED: ING5‐mediated antineuroblastoma effects of suberoylanilide hydroxamic acid - Ji‐cheng Wu; Hua‐mao Jiang; Xiang‐hong Yang; Hua‐chuan Zheng (Cancer Medicine)
Abstract Neuroblastoma is the most common extracranial solid neuroendocrine cancer and is one of the leading causes of death in children. To improve clinical outcomes and prognosis, discovering new promising drugs and targeted medicine is essential. We found that applying Suberoylanilide hydroxamic acid (SAHA; Vorinostat, a histone deacetylase inhibitor) and MG132 (a proteasome inhibitor) to SH‐SY5Y cells synergistically suppressed proliferation, glucose metabolism, migration, and invasion and induced apoptosis and cell cycle arrest. These effects occurred both concentration and time dependently and were associated with the effects observed with inhibitor of growth 5 (ING5) overexpression. SAHA and MG132 treatment increased the expression levels of ING5, PTEN, p53, Caspase‐3, Bax, p21, and p27 but decreased the expression levels of 14‐3‐3, MMP‐2, MMP‐9, ADFP, Nanog, c‐myc, CyclinD1, CyclinB1, and Cdc25c concentration dependently, similar to ING5. SAHA may downregulate miR‐543 and miR‐196‐b expression to enhance the translation of ING5 protein, which promotes acetylation of histones H3 and H4. All three proteins (ING5 and acetylated histones H3 and H4) were recruited to the promoters of c‐myc, Nanog, CyclinD1, p21, and p27 for complex formation, thereby regulating the mRNA expression of downstream genes. ING5 overexpression and SAHA and/or MG132 administration inhibited tumor growth in SH‐SY5Y cells by suppressing proliferation and inducing apoptosis. The expression of acetylated histones H3 and ING5 may be closely linked to the tumor size of neuroblastomas. In summary, SAHA and/or MG132 can synergistically suppress the malignant phenotypes of neuroblastoma cells through the miRNA‐ING5‐histone acetylation axis and via proteasomal degradation, respectively. Therefore, the two drugs may serve as potential treatments for neuroblastoma.